Investigation of Thermal-Hydraulic Performance in Flat Tube Heat Exchangers at Various Tube Inclination Angles - A. Y., Adam; A. N., Oumer; Azri, Alias; M., Ishak; M. M., Noor (Universiti Malaysia Pahang, 2017)
The performance of compact fin-and-flat tube heat exchangers (HE) can be affected by many geometrical and processing factors and one of them is tube inclination angle. However, the effect of flat tube inclination angle on the thermal-hydraulic performance of the HE is not fully examined. This paper investigates the effects of flat tube inclination angles on heat transfer and pressure drop characteristics of fined flat tube HE when the tubes are deployed in in-line and staggered arrangements. A symmetric numerical method based on FLUENT software was carried out with six different tube inclination angles (0°, 30°, 60°, 90°, 120°, and 150°) in moderately high Reynolds number. From the results, it was observed that heat transfer coefficient increased with the augmentation of the tube inclination angle from 0o to 90o and decreased for 120o and 150o. With the increase of tube inclination angle, the average Nusselt number rose by 36.3%. This might be due to the reason that the tube surface area increases with the inclination angle, which also results in the largest increment of the pressure drop by 42.0%. Overall, the 90o tube inclination angle showed the highest enhancement in heat transfer for both inline and staggered configurations with a maximum enhancement of 41.2% for in-line and 32.2% for staggered arrangements. However, the heat transfer enhancements were accompanied by high-pressure drop penalties of up to 44.2% and 42.6% for in-line and staggered arrangements, respectively. Therefore, inclining the tubes at 90o is recommended where high heat transfer is required. On the other hand, 0o tube inclination angle is recommended where pumping power is a crucial issue.